Expanding the Possibilities of Modeling Signals of Telecommunications and Radioelectronics Systems - V. A. Ilyinkov; Y. S. Maisiyevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The special procedure for the formation of reference values for a set of signals from telecommunication and radioelectronic systems (STR) has been developed based of the proposed library of auxiliary functions, which provides simplicity, ease of use and significantly expands the possibilities of signal modeling. An operator model of the response of an arbitrary linear system to a composite trapezoidal (periodic, non-periodic finite) signal is constructed. The mathematical model (in the time domain) of the linear system reaction to a set of the STR signals has been built, varying in form, time of existence, and method of assignment. The unified algorithm for mathematical modeling of linear distortions of the STR signals has been developed. In accordance with the latter, an ease of use of the program for mathematical modeling of the STR signal set in the time domain has been developed, representing the investigated reaction in graphical (with the ability to scale along the axes), tabular, and file forms.